2020
DOI: 10.11591/edulearn.v14i3.16342
|View full text |Cite
|
Sign up to set email alerts
|

Availability and utilization of e-learning facilities in the teaching of Senior School Physics in Ilorin, Nigeria

Abstract: The study was intended to examine the utilization as well as the availability of E-learning facilities in the teaching of senior school physics in Ilorin, Nigeria. The study was a survey type and all physics teachers constitute the population. A total of 60 teachers was sampled for the study. Multi-stage sampling technique was adopted in the selection of respondents. Simple random sampling technique was used to select 20 out of 35 secondary schools. Two structured checklists were used to collect data. Percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Teaching Practices; this building block was harder to make since trainers have to turn teachers from their traditional framework, even someone who does not want to unfreeze. It was learnt that availability of resources alone will not change teacher's perspective [10]. In this respect, analyzed inspections were used for identifying their weak points and provide solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching Practices; this building block was harder to make since trainers have to turn teachers from their traditional framework, even someone who does not want to unfreeze. It was learnt that availability of resources alone will not change teacher's perspective [10]. In this respect, analyzed inspections were used for identifying their weak points and provide solutions.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Nigeria to estimate the availability and the utilization of E-learning facilities in the teaching of physics in senior school revealed that although the resources were available it did not make any significant effect on the teaching of the subject [10]. The teachers' qualifications nor experience also had no effect on the utilization of the e-resources.…”
Section: State Of the Artmentioning
confidence: 99%
“…In the current study, the participants also indicated their relatively high level of satisfaction with learning environment. To ensure the quality of online instruction, the online learning facilities should be user-friendly and updated (Akanbi, 2020). It is not unexpected that Internet connection problem led to the lowest level of learners' satisfaction; however, "online support from teachers and technical team is good", gaining the highest level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…(Borthwick & Plutino, 2020), Notwithstanding the key role played by e-learning in improving the teaching and learning process, there is the problem of inadequate knowledge about using e-learning in teaching students in school (Innocent & Masue, 2020). And based on the results of many studies that showed that there are many obstacles in adopting elearning in schools, such as the study of Meirovitz & Aran (2020), Apostolou (2020), Bigirwa, Ndawula, Naluwemba (2020), Akanbi (2020), Alqahtani & Rajkhan (2020), Siron, Wibowo, & Narmaditya (2020), Hariyanto, Triyono & Kohler (2020), Mailizar, Maulina & Bruce (2020), Innocent & Masue (2020) and Shdaifat, Shdaifat & Khateeb (2020).…”
Section: Problem and Questions Of The Studymentioning
confidence: 99%